Reproductive stage associated changes in plasma fatty acid profile and proinflammatory cytokine expression in rat mammary glands - Sen Lin (Animal Nutrition, 2016)
Mastitis is a common disease for mammals all around the world. Figuring out why mastitis mainly occurs around parturition may be helpful for dealing with the disease. Lipolytic activity and oxidative stress take place around parturition, which may leads to alteration in fatty acids profile and proinflammatory cytokine expression. Thus, the aim of the present study was to further our understanding about the high incidence of mastitis around parturition by comparison of plasma fatty acid profile and mammary inflammation indicators at different reproductive stages. A total of 47 female rats were included in the present study. After mating, all the pregnant and non-pregnant rats began to receive the same experimental diet. Blood samples were collected at day 1 and 14 of gestation as well as day 3 postpartum. Mammary samples were collected at day 14 of gestation and day 3 postpartum from pregnant and non-pregnant rats. The results showed that rats at d 3 postpartum had greater (P < 0.05) plasma concentrations of non-esterified fatty acids (NEFA), arachidonic acid (ARA) and docosahexaenoic acid (DHA) as well as ARA: eicosapentaenoic acid (EPA) ratio than those at d 14 of gestation. The mRNA abundances of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), IL-8 and xanthine oxidoreductase (XOR) in mammary of the pregnant rats were greater (P < 0.05) than those in age-matched non-pregnant rats. Rats at d 3 postpartum had higher (P < 0.05) protein expression levels of IL-1β and TNF-α as well as meloperoxidase (MPO) activity and polymorphonuclear neutrophils (PMN) prevalence than those at d 1 of gestation. The rats at d 3 postpartum also had greater (P < 0.05) IL-1β and MPO activity than those at d 14 of gestation. The results indicated that elevated mammary expression of proinflammatory cytokines and XOR as well as altered fatty acid profile around parturition might facilitate the recruitment of neutrophils into mammary glands.